Pertumbuhan Lobster Air Tawar (Cherax Quadricarinatus) yang Diberi Pakan Pasta Berupa Campuran Pelet, Keong, dan Singkong - Saepul Miptah; Novita MZ; Arif Supendi (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2024)
Crayfish is one of the fishery commodities that has high economic value, behind having high economic value in lobster cultivation there are several things that need to be considered, namely the conditions of the cultivation environment, feed, and water quality, based on the findings in the field of crayfish cultivators inukabumi have innovations in feed making, this is done to reduce feed production costs, the feed innovation is a mixture of pellets, conch and cassava, with a ratio of comparison in tub 1 P: 1 K: 1 S: 1.4 tub 2 P: 1, K: 1.4 S.: 1, and tub 3 100% pellets, this feed has never been tested to determine the nutritional content of the feed, in this study conducted to test the effectiveness of feed for crayfish growth, while the test results show that the proximate value in tub 1 is 20.55% Protein, tub 2 is 14.32% Protein and tub 39.41% Proterin in this study conducted 3 tubs and each stocked 100 e / tub, this study was conducted for 14 days of maintenance, and feeding is done 2 times a day, the results of this study indicate that the survival rate is low, with SR values in tub 1, (22%) tub 2, (23%) and tub 3 (10%), this is influenced by inappropriate feed, and water quality that is not in accordance with predetermined quality standards, and during the maintenance of crayfish many were found dead due to molting failure with a size of> 9.2 cm, so that the feed used is inappropriate